Telemedical Interventional Management in Heart Failure II (TIM‐HF2), a randomised, controlled trial investigating the impact of telemedicine on unplanned cardiovascular hospitalisations and mortality in heart failure patients: study design and description of the intervention. (19th September 2018) - Koehler, Friedrich; Koehler, Kerstin; Deckwart, Oliver; Prescher, Sandra; Wegscheider, Karl; Winkler, Sebastian; Vettorazzi, Eik; Polze, Andreas; Stangl, Karl; Hartmann, Oliver; Marx, Almuth; Neuhaus, Petra; et al.
Abstract : Background: Heart failure (HF) is a complex, chronic condition that is associated with debilitating symptoms, all of which necessitate close follow‐up by health care providers. Lack of disease monitoring may result in increased mortality and more frequent hospital readmissions for decompensated HF. Remote patient management (RPM) in this patient population may help to detect early signs and symptoms of cardiac decompensation, thus enabling a prompt initiation of the appropriate treatment and care before a manifestation of HF decompensation. Objective: The objective of the present article is to describe the design of a new trial investigating the impact of RPM on unplanned cardiovascular hospitalisations and mortality in HF patients. Methods: The TIM‐HF2 trial is designed as a prospective, randomised, controlled, parallel group, open (with randomisation concealment), multicentre trial with pragmatic elements introduced for data collection. Eligible patients with HF are randomised (1:1) to either RPM + usual care or to usual care only and are followed for 12 months. The primary outcome is the percentage of days lost due to unplanned cardiovascular hospitalisations or all‐cause death. The main secondary outcomes are all‐cause and cardiovascular mortality. Conclusion: The TIM‐HF2 trial will provide important prospective data on the potential beneficial effect of telemedical monitoring and RPM on unplanned cardiovascular hospitalisations and mortality in HF patients. Trial registration:ClinicalTrials.gov Identifier NCT01878630.